Advanced Esthetic Management of Dental Implants: Surgical and Restorative Considerations to Improve Outcomes. Issue 4 (14th July 2015) - Levin, Barry P.; Rubinstein, Sergio; Rose, Louis F.
Abstract Objective Successful dental implant therapy in the maxillary anterior dentition requires meticulous attention to surgical and prosthodontic measures. Clinical Considerations Proper diagnosis, extraction technique, implant selection, and placement significantly impact outcomes. Respect of hard and soft tissue physiology following tooth loss and implant placement requires specific steps be taken. Management tissue contours properly, via regenerative therapy, results in successful framing of the restoration. Provisionalization and definitive restorative therapy also impacts the level of esthetic success. The contours of the temporary abutment and crown develop soft tissue contours for the final restoration. Overcontouring can lead to soft tissue recession and mucosal asymmetry. Design of the definitive crown(s) is crucial for long‐term maintenance of esthetically acceptable results. Conclusion Visualizing the outcome of treatment prior to its inception, following specific surgical and restorative guidelines, increases the likelihood of success. Clinical Significance This article demonstrates the importance of proper surgical and prosthetic principles in achieving esthetic implant results.